METHODS FOR REDUCING THE DURATION OF OSSEOINTEGRATION IN DENTAL IMPLANTOLOGY - Nazarov Umidjon Usmonovich (Modern American Journals, 2025)
This article reviews practical methods to reduce osseointegration time in dental implantology: implant surface modifications (micro-roughness, hydrophilicity, bioactive coatings), biomaterial choices (titanium, zirconia, PEEK-based solutions), photobiomodulation (low-level laser therapy), and biological adjuncts (PRP/PRF, BMP-2, growth factors). Combined, these approaches may accelerate early bone formation, improve implant stability, and enable earlier functional loading. Key limitations include safety considerations, protocol standardization, and cost-effectiveness.
Keywords: Osseointegration; implant surface; hydrophilicity; laser therapy; PRP/PRF; BMP-2; titanium; zirconia.